REALITAS SOSIAL DALAM NOVEL SEMBILAN KEBODOHAN SOBRY KARYA YOSSIE ENES: KAJIAN SOSIOLOGI SASTRA - Aldi Ibrahim; Rasiah Rasiah; Afriani Ulya (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2026)
This study aims to describe the social realities depicted in the novel Sembilan Kebodohan Sobry by Yossie Enes using Alan Swingewood's sociology of literature. This approach views literary works as social documents that reflect societal dynamics, including economic, political, cultural, and everyday life aspects. The study employs a qualitative descriptive method with a literature study technique. Data were collected through intensive reading and note-taking, focusing on excerpts in the novel that represent social realities. The analysis was conducted by classifying and interpreting these excerpts based on relevant sociological categories. The results indicate that the novel Sembilan Kebodohan Sobry contains five forms of social reality: (1) social and economic inequality, depicting the conditions of the lower-class society; (2) the struggle of Indonesian migrant workers, portraying the lives of female workers striving to earn a living abroad; (3) corruption and bureaucracy in the government, illustrating the weakness of the bureaucratic system in society; (4) culture and tradition, showing how cultural and traditional values are altered due to the influence of power; and (5) religion and mysticism, revealing the shift from a pure and sacred concept of religion to one that is politicized and manipulated. Thus, this novel is not only a narrative fiction but also a powerful medium of social criticism. It affirms the role of literature as both a mirror and a critique of the society in which it is born.